2013
DOI: 10.1002/adfm.201203427
|View full text |Cite
|
Sign up to set email alerts
|

Real‐Time Microscopy of Reorientation Driven Nucleation and Growth in Pentacene Thin Films on Silicon Dioxide

Abstract: The role of molecular reorientation processes in the self‐assembly of anisotropic molecules, such as pentacene (Pn) is studied utilizing a unique capability of low‐energy electron microscopy (LEEM) for the real‐time investigation of the film growth. In Pn film on SiO2, a layer‐by‐layer growth is observed, albeit different from the expected Volmer–Weber growth mode typical for the systems with lower adhesion (weak interfacial interaction). The observed growth mechanism is also different than conventional concep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
43
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 48 publications
1
43
2
Order By: Relevance
“…This introduces an attachment barrier E at . In our previous reports on growth of films made of anisotropic molecules [20,34], where the molecules prefer to be at different orientations at diffusive state (lying down) than that in crystalline islands (standing up), we found that the energy barrier for molecule reorientation causes a delay in the nucleation of crystalline islands. In that experimental system the incorporation-limited growth model was proposed.…”
Section: Resultsmentioning
confidence: 61%
See 2 more Smart Citations
“…This introduces an attachment barrier E at . In our previous reports on growth of films made of anisotropic molecules [20,34], where the molecules prefer to be at different orientations at diffusive state (lying down) than that in crystalline islands (standing up), we found that the energy barrier for molecule reorientation causes a delay in the nucleation of crystalline islands. In that experimental system the incorporation-limited growth model was proposed.…”
Section: Resultsmentioning
confidence: 61%
“…The shape anisotropy of a planar molecule such as phthalocyanine is expected to make its aggregation processes complex, in a similar fashion to film growth of other anisotropic molecules [17][18][19][20]. Moreover, the metal center is accessible from both sides of the molecular plane.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the LSMO surface looks completely covered when a 3 nm pentacene film is deposited at 30 C, the coverage is not complete and the wetting layer disappears when pentacene is deposited above 40-45 C. The thermal energy at 40-45 C is sufficient to overcome the interaction of pentacene molecules with the substrate, while on SiO 2 a temperature of at least 80 C is needed. 24 The flat morphology over a large area shown in Figures 3(b)-3(e) has been previously observed only on SiO 2 , and only when the growth was assisted by a supersonic gas flow that gave molecules a high kinetic energy and hence a high surface diffusivity. 30 The analysis of the effective coverage, obtained by measuring the volume of the islands, 15 shows that it decreases from 75% at a substrate temperature of 45 C to 55% at 75 C: at this temperature desorption could start to play a significant role.…”
mentioning
confidence: 82%
“…23 ES barrier-controlled growth leads to a three dimensional growth which results in a roughening of the film. 24 This roughening is called "rapid" because it grows with the film thickness faster than in the random deposition model (RD), where molecules attach where they arrive, without diffusion. 25 In general, it is valid that R rms $ t b , where t is the nominal film thickness and b is the growth exponent; in the RD model b ¼ 0.5.…”
mentioning
confidence: 99%